Effects of ripening on rheological properties of avocado pulp (Persea americana mill. Cv. Hass). (April 2015) - Osorio, F; Roman, A; Ortiz, J
Abstract: Avocado (Persea americana Mill) Hass variety is the most planted in Chile with a greater trade prospect. The aim of this study was to investigate the effect of maturity on rheological properties of Chilean Avocado Hass pulp. Fresh unripe avocados were washed and peeled, cut and stored at 3 different times; a portion was treated at 5°C and the other was treated at 20°C until it reached 2 lb puncture pressure. During maturation changes would develop due to temperature and time, with internal cellular structure changes. Preliminary results of the rheological characteristics of avocado puree show a Bingham plastic behavior.